Peran Pemerintah Desa Bendosewu dalam Pengelolaan Badan Usaha Milik Desa (Bumdes) di Desa Bendosewu Kec. Talun Kab. Blitar - Irma Dhatul Aulia; Deby Febrian Eprilianto; Galih Wahyu Pradana; Melda Fadiyah Hidayat (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research is motivated by the gap between normative conditions and the reality of BUMDes Sewu Siji management. The purpose of this study is to describe the role of the Bendosewu Village Government in managing BUMDes Sewu Siji. This research employs a descriptive qualitative approach with data collection through interviews, observation, and documentation. Data analysis uses the interactive model by Miles, Huberman, and Saldana with the role theory framework from John M. Ivancevich, Robert dan Michael T. Matteson (1990) which divides roles into three dimensions: Expected Role, Perceived Role, and Role Played. The results show that in the Expected Role dimension, the normative role is fairly well defined, although there is a weakness in defining the role of the Village Secretary which becomes the root of role ambiguity. In the Perceived Role dimension, variations in understanding among actors were found; the Village Head as the central actor, while the Village Secretary, BPD, and Village Treasurer perceive their roles as limited. In the Role Played dimension, four role problems were identified: role gap, role ambiguity, role underload, and role conflict. This study also found a discrepancy between official BUMDes Clinic data and field facts, where BUMDes Sewu Siji has had a legal entity, RPK, and annual reports although not officially recorded. This study concludes that the role of the Bendosewu Village Government is not yet optimal due to misalignments between normative expectations, perceptions, and actual practices which give rise to role dysfunctions. This condition leads to the dominance of the Village Head's role and suboptimal utilization of other village apparatuses' potential.